1998
DOI: 10.1136/adc.79.2.126
|View full text |Cite
|
Sign up to set email alerts
|

Randomised controlled trial of brief neonatal exposure to cows' milk on the development of atopy

Abstract: Objective-To determine the eVect of brief early exposure to cows' milk on atopy in the first 2 years of life. Design-Double blind, placebo controlled, randomised feeding intervention trial (Bokaal study). Setting-Dutch midwifery practices. Participants-1533 breast fed neonates. Intervention-Exposure to cows' milk protein (n = 758) or a protein free placebo (n = 775) during the first 3 days of life. Main outcome measures-Clinical atopic disease and any positive radioallergosorbent (RAST) tests at 1 year of age.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
1
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(59 citation statements)
references
References 7 publications
1
56
1
1
Order By: Relevance
“…Similar data have been reported in case and control studies [34], a series of case studies [25], and cohort studies [24,35,36]. However, De Jong et al [26] refuted this association in a double-blind randomized trial of 1,533 infants who were given either CMP or a placebo for 3 days and were monitored for the occurrence of atopic diseases for 2 [26] and 5 years [27]. The authors concluded that early exposure to CMP was not associated with atopic diseases.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…Similar data have been reported in case and control studies [34], a series of case studies [25], and cohort studies [24,35,36]. However, De Jong et al [26] refuted this association in a double-blind randomized trial of 1,533 infants who were given either CMP or a placebo for 3 days and were monitored for the occurrence of atopic diseases for 2 [26] and 5 years [27]. The authors concluded that early exposure to CMP was not associated with atopic diseases.…”
Section: Discussionmentioning
confidence: 49%
“…There is also not much evidence regarding the use of special formulas [15,16], probiotics [17], or prebiotics [18] by patients at risk. Other factors that have been studied are caesarean delivery [19,20,21,22,23] and perinatal exposure to small amounts of CMP [24,25,26,27], though the results are conflicting. Other factors such as duration of BF [14,28,29], prematurity, threatened premature delivery, preeclampsia [30], hypertension, gestational diabetes [31], and antibiotics [21] during labor have been much less studied.…”
Section: Introductionmentioning
confidence: 96%
“…The effects of soy formula were evaluated by 1 systematic review 59 and 1 RCT. 94 Three RCTs [106][107][108] evaluated neonatal exposure to cow's milk on 2 distinct populations. Hydrolyzed formulas (particularly extensively and partially hydrolyzed formulas) may reduce infant and childhood cow's milk allergy in high-risk infants when compared with cow's milk formula.…”
Section: Maternal Diet During Pregnancy or Lactation Maternal Diet Dmentioning
confidence: 99%
“…We also excluded studies by Chandra et al 65 , given published reports that question the validity of those data. 87,88 The studies meeting inclusion criteria evaluated 5 prevention strategies: breastfeeding and delayed introduction of solids (2 studies 89,90 ), maternal diet during pregnancy or lactation (3 studies 58, 91,92 ), exclusive breastfeeding (3 studies 93,95,110 ), special diets in infants and young children (12 studies 59-61,94,96-100, [106][107][108] ), and probiotics (5 studies [101][102][103][104][105] ) (eTable 2). Breastfeeding and Delayed Introduction of Solids.…”
Section: Prevention Of Food Allergies and Atopic Eczemamentioning
confidence: 99%
“…This was summarized in a recent meta-analysis [26]. Only some of these studies have looked at food allergy using clinical history and skin prick/specific IgE end points, as summarized in Table 1 [27][28][29][30]. Only one study was truly randomized [27].…”
Section: Breast-feedingmentioning
confidence: 99%